Molecular Virology of KSHV in the Lymphocyte Compartment—Insights From Patient Samples and De Novo Infection Models - Aalam, Farizeh; Totonchy, Jennifer (Frontiers in Cellular and Infection Microbiology, 2020)
The incidence of KSHV-associated Kaposi Sarcoma has declined precipitously in the present era of effective HIV treatment. However, KSHV-associated lymphoproliferative disorders continue to be a source of morbidity and mortality in people living with HIV (PLWH). Lymphoma is a leading cause of death in PLWH, indicating that the immune reconstitution provided by antiretroviral therapy is not sufficient to fully correct the immune dysregulation perpetrated by HIV infection. As such, novel insights into the mechanisms of KSHV-mediated pathogenesis in the immune compartment are urgently needed in order to develop novel therapeutics aimed at prevention and treatment of KSHV-associated lymphoproliferations. In this review, we will discuss our current understanding of KSHV molecular virology in the lymphocyte compartment, concentrating on studies which explore mechanisms unique to infection in B lymphocytes.